SYAIR NYANYIAN KRISTEN SEBAGAI LANDASAN PENGAJARAN IMAN BAGI ANAK DI SEKOLAH - Rivanny Clara Lekatompessy; Marthcelina Manuputty (STKIP Subang, 2026)
This article explores Christian hymn lyrics as a foundation for teaching children's faith in schools. Christian hymns are an important tool for connecting with and communicating with God. The lyrics of Christian hymns convey messages of faith. Furthermore, they are also useful for conveying spiritual and ethical values ​​that can be applied in life. In schools, teaching faith can be taught through Christian hymn lyrics. Educators use this singing technique because singing makes it easier for children to understand and remember, and it can improve their learning mood, thus enabling them to absorb lessons effectively. Through Christian hymns, children can interpret each lyric and develop their faith experience. Through these lyrics, children can also be taught spiritual and ethical values ​​in their lives. The words contained in each lyric of Christian hymns can aid the teaching of religious education in schools. The method used in writing this article is a literature review, using various literature sources to obtain information for this research.